Analyte sensing with unselectively binding synthetic receptors: virtues of time-resolved supramolecular assays. Issue 100 (30th November 2022) - Prabodh, Amrutha; Sinn, Stephan; Biedermann, Frank
Abstract : Time-resolved supramolecular assays probe analyte-characteristic complexation and decomplexation rates. Consequently, even unselectively binding synthetic receptors can be used for analyte identification and quantification. Abstract : The cross-reactivity to many analytes is one major limitation of most synthetic receptors (SRs) known so far. Herein, we show that through time-resolved competitive binding assays, even unselectively binding SRs can be utilized for analyte distinction and quantification. Furthermore, our methodology has also been applied to analyte mixtures and can be used in a microplate format.